The Truth of the Matter: A Defense of Critical Thinking as the Principle Aim of Education - Sawaya, Vincent (Stance: an international undergraduate philosophy journal, 2012)
With the rise of state sponsored standardized testing and curriculum alignment, it is important to consider the impact such practices may have on educational aims. In this paper, I argue that critical thinking ought to be the principle aim in every educational pursuit, and that practices such as “teaching to the test” may be detrimental to its development. I maintain these claims with a discussion of the philosophical works of Harvey Siegel, Israel Scheffler, and John Dewey. Operating from their definitions of critical thinking, rationality, and education respectively, I offer support for my conclusion based on one’s ability to challenge the soundness of claims, and the revisional quality of true belief. The issue of critical thinking as general or subject specific is also addressed. Using Siegel’s notion of a critical spirit, I propose that a universal quality of critical thinking lies in its normative as opposed to technical aspects.